Underutilization of coper/non-coper screening in anterior cruciate ligament injuries management in Italy: an online survey - Macrelli, Luca; Mallia, Luca; Thiebat, Gabriele; Rocchi, Jacopo Emanuele; Herrington, Lee; Nutarelli, Sebastiano (Frontiers in Rehabilitation Sciences, 2025)
IntroductionTotal and sub-total lesions of the anterior cruciate ligament (ACL) are one of the most frequent and performance-limiting injuries to the knee joint within the active population. Early surgical management, often regarded as the primary management strategy, has recently been shown to have similar outcomes when compared with an initial rehabilitative approach followed by surgical ACL reconstruction if higher levels of functionality are needed. The primary objective of the study was to investigate the physiotherapists and orthopedic surgeons’ “coper/non-coper” screening application in the clinical management of the patient after ACL injury. Second, the authors aimed to investigate the cooperation between physiotherapists and orthopedic surgeons when dealing with patients with ACL injuries.MethodsAn online survey consisting of 12 questions on the clinical practice of the surveyed physiotherapists (n = 803) and orthopedic surgeons (n = 201), and the relation between these healthcare professionals, was distributed. The answers were stratified depending on clinical experience in dealing with ACL injuries.ResultsBoth physiotherapists and orthopedic surgeons showed a low degree of confidence and application of the “coper/non-coper” screening when managing ACL lesions. The sub-population of ACL experts reported a good level of interprofessional interaction. Nevertheless, an updated level of knowledge regarding the recent evidence on the non-surgical management of ACL lesions is still lacking.ConclusionsThe study findings indicate the need to improve the collaboration between Italian physiotherapists and orthopedic surgeons as well as their knowledge of the non-surgical approaches to ACL lesions.